APLIKASI PENGAJARAN TAUHID DALAM KELUARGA SEBAGAI SOLUSI MENGATASI PERMASALAHAN KENAKALAN REMAJA - Adam Sugiarto; Rahmatullah Rusli; Mudzakir Mudzakir; Fathudin Ali; Nurjaya Nurjaya (Abdimisi, 2019)
Various social problems that arise in social life, especially among adolescents who are influenced by the rapid development of technology from time to time, the world of adolescents is an easy target of the bad influence of this technology because they can easily get everything from their gadgets, starting from the open. the breadth of the world of friendship to easy access to negative content such as pornography, radicalism, which can then drag teenagers to promiscuity, drugs, brawl and so on. The lack of knowledge of orangutans in understanding and overcoming these problems makes them unable to direct their children to avoid various negative influences of association and technology. On the basis of the desire to share and provide solutions to this, this PKM is carried out with the aim of increasing understanding and knowledge of parents in overcoming and fortifying their children from the negative influence of socialization and technology by strengthening tauhid education in the family.Keywords: Teaching; Tawheed; Youth; Family<p